A computational fluid dynamic study of supersonic beveled nozzle jets - Tay, Sarah Ching Wen (2017)
Supersonic flow emanating from a 30○ and 60○ beveled nozzle jet at an under-expanded condition was examined. In this numerical study, a 2D Unsteady Reynolds-Averaged Navier–Stokes (URANS) simulation was conducted, followed by a 3D Large Eddy Simulation (LES). The 2D URANS study involved an initial mesh dependency check to test for the level of convergence using meshes of different grid sizes. Subsequently, the 30○ beveled nozzle was subjected to under-expansion at various Nozzle Pressure Ratios (NPR) of 3.4, 4.0 and 5.0 to produce supersonic flow with an exit Mach number of 1.33. In the 3D LES study, supersonic flow through a 60○, under-expanded beveled nozzle at NPR = 4.0 and Total Temperature Ratio (TTR) of 1.0 was simulated up to a flow time of 1.100ms. A small time-step of 1e-08s was utilized to capture small flow fluctuations. The simulation was then run on High Performance Computers (HPC) to speed up the process. Results from these simulations were compared with past physical and numerical experimental data for validation of the current study. While the shock structures from the 2D simulations were similar to those from other studies, the numerical values lack accuracy. On the other hand, results from the 3D study corroborate with existing numerical and experimental data, in terms of the deflected angles and shock structures. This paper concludes with some possible directions to aid in understanding how flow features may be altered with different set-ups or flow conditions.